Development of an Adaptive Slicing Algorithm of Laminated Object Manufacturing Based 3D Printing for Freeform Formwork - Dongyoun Lee; Junho Hong (Buildings, 2022)
Recently, as “Freeform buildings” have increased in number, studies on ways to increase productivity in the construction of freeform buildings are increasing. In the case of 3D printing in construction, many studies are being conducted using the material extrusion method; among the 3D printing methods, manufacturing freeform forms using laminated object manufacturing (LOM) can overcome the limitation presented above. However, there is a lack of cases used in LOM construction sites, so it is necessary to increase the productivity of construction work and study the slicing method suitable for construction. Therefore, in this paper, we propose using study criteria and adaptive slicing methods to combine both the shape error and the manufacturing time of freeform construction. A case study was conducted to verify the results of this study; the freeform concrete form manufacturing with the algorithm that proposed this study could save 66.1% of the manufacturing time compared with CNC milling, and it needs 19.8% less manufacturing time than the existing uniform slicing method. This is a result of the production of one freeform form, and it can be expected to have a greater effect if applied to many freeform forms used in construction sites. In addition, the results of this study can be used as a decision-making tool that can determine the shape and manufacturing time of production according to the on-site situation.